2006
DOI: 10.3168/jds.s0022-0302(06)72563-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Bioactivity of Recombinant Human Lysozyme in the Milk of Transgenic Mice

Abstract: Human milk lysozyme is an important protein for innate immunity, but human breast milk is a fairly poor source for commercial production of this enzyme. Research on the expression of recombinant human lysozyme (rHlys) is therefore potentially valuable to the dairy industry. In this study, 2 different kinds of transgenic mice, PBC-hLY and PBC-sighLY, were generated and used as system models to express rHlys. Six lines of PBC-hLY transgenic mice with human lysozyme genomic DNA-based constructs were generated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…Recently, the production of transgenic dairy goats producing human lysozyme in their milk was reported (Maga et al 2006). Our previous studies showed that the plasmid pBC1-hLZ-GFP-Neo can express bioactive rhLZ in the milk of transgenic mice (Yu et al 2006) which warrants us to further investigate the feasibility of the strategy for producing rhLZ transgenic pigs.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the production of transgenic dairy goats producing human lysozyme in their milk was reported (Maga et al 2006). Our previous studies showed that the plasmid pBC1-hLZ-GFP-Neo can express bioactive rhLZ in the milk of transgenic mice (Yu et al 2006) which warrants us to further investigate the feasibility of the strategy for producing rhLZ transgenic pigs.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have shown that the goat -casein promoter can efficiently direct the high expression of a foreign gene in the milk of transgenic animals, such as human serum albumin (up to 40 g/L) in bovine milk (Echelard et al, 2009) lysozyme (up to 1.45 g/L) in transgenic mice (Yu et al, 2006) and lactoferrin ( 2.5 g / L and 3.4 g / L) in two transgenic cows . The levels of recombinant protein expression reported in those studies were high, suggesting that the goat -casein gene promoter is a successful expression system.…”
Section: Construction Of a Recombinant Lr-his Tag Gene Expression Vecmentioning
confidence: 99%
“…On the other hand, deletion from the β-casein gene of exon regions responsible for the formation of the protease (plasmin) site in its translation product can induce an increase in β-casein emulsifying properties as well as elimination of the bitter flavour in produced cheese (Hitchin et al 1996, Laible et al 2007, Pampel et al 2008. Introduction of supplementary functional copies of genes encoding regulatory immunoproteins of the milk such as lysozyme, lactoferrin or lysostaphin can enhance the antimicrobial immunosupressive activity of such genetically-modified milk (Hyvö nen et al 2006, Yu et al 2006). …”
Section: The Perspectives Of Somatic Cell Cloning and Transgenesis Ofmentioning
confidence: 99%
“…It has been found that the biochemical composition of human milk differs considerably from the composition of both the milk of cattle and of small ruminants. Human milk contains much less total protein (10 g/l) than cow's milk (33 g/l), 70% of which consists of the fraction of whey proteins including, above all, lactoferrin and lysozyme (i.e., mucopeptide glycohydrolase) (Hyvö nen et al 2006, Yu et al 2006). In contrast to bovine milk, the concentration of caseins in human milk is considerably lower.…”
Section: The Perspectives Of Somatic Cell Cloning and Transgenesis Ofmentioning
confidence: 99%